Design of Automatic Brick Dough Mixer Using 1 Phase AC Induction Motor - Santosa, Yoga Dwi; Aji, Wahyu Sapto (Association for Scientific Computing Electrical and Engineering (ASCEE), 2020)
Bricks are the main component in a building, the increasing demand for bricks makes bricks sought after by the public so craftsmen have to produce enough bricks to meet market needs. From this problem, a design of an automatic brick dough mixer using a 1-phase AC induction motor was made, a concept design was carried out for making tools. In making the tool, the most important component of this research is the 1 phase AC induction motor where this motor will work to stir a dough so that it is evenly mixed. So that the humidity level of the dough can be measured with a moisture sensor, what is the level of density in a brick mixture that is made. To test the humidity level so that the dough becomes dense, 3 L of water and 9 L of soil are obtained at a temperature of 63%, the average cut in one minute is 24 bricks and for manual manufacture it produces 3 bricks in one minute so that it can be obtained conclusion with this tool the brick craftsmen can be helped to speed up production results in order to obtain efficiency in work results.